PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA DENGAN MENGGUNAKAN MODEL CREATIVE PROBLEM SOLVING (CPS) - Ika Diana; M. Syahrul Rizal; Iis Aprinawati; Mohammad Fauziddin; Rizki Ananda (Jurnal Dedikasi Pendidikan, 2024)
This research aims to improve the critical thinking skills of class IV MI Baitul Haq Bumi Mulya students in the 2022/2023 academic year, which consists of 15 students. This research method is Classroom Action Research (PTK) which is carried out in two learning cycles. Each cycle consists of two meetings and four learning stages, namely: planning, implementing, observing, and reflecting. When the research was carried out in May 2023. Data collection techniques were in the form of documentation, observation and tests. The results of the critical thinking skills of grade IV MI Baitul Haq Bumi Mulya students in the pre-action average value of 72.53 with a proportion of learning completeness of 40%. At the meeting of cycle 1 the average value was 49.33 with a proportion of learning completeness of 40% and in cycle 1 of meeting II there was an increase with an average value of 63.86 with a proportion of learning completeness of 53%. At the cycle 2 meeting there was also an increase with an average score of 80.06 with a proportion of learning completeness of 67%, and at the cycle 2 meeting there was an increase again with an average score of 82.13 with a proportion of learning completeness of 87%. Thus it can be concluded that the application of the Creative Problem Solving (CPS) learning model can improve the critical thinking skills of class IV MI Baitul Haq Bumi Mulya students.